Perceived Restaurant Food Healthiness on Consumer Satisfaction at Burgreens Menteng Resto - Ni Made Dwiyana Rasuma Putri; Jessica Tritanya; Rieke Rinova (The Postgraduate School of Tourism Sahid Polytechnic, 2023)
This research aims to look for the significance of the effect of perceived restaurant food healthiness on consumer satisfaction at Resto Burgreens Menteng. The respondents of this research are consumers of the Burgreens Menteng restaurant using a sample of 318 people. The sampling technique used was non-probability sampling with an accidental sampling approach. Data analysis using IBM SPSS application ver. 25 for Windows, using the technique of Simple Linear Regression Analysis. The results of this research indicate that perceived restaurant food healthiness is proven to have a positive and significant effect on consumer satisfaction. The role of perceived restaurant food healthiness is directly proportional to consumer satisfaction. The implications of this research support the results of previous research and strengthen the theory related to perceived restaurant food healthiness and consumer satisfaction. Perceived restaurant food healthiness has an important role in consumer satisfaction in a restaurant. changing views about eating. Besides to fulfill the daily needs of humans, food also must make the body healthy. So, avoid being overweight and avoid various types of diseases. Keywords: perceived food healthiness, restaurant, consumer satisfaction.